An analysis of environmental and economic impacts of the system of rice intensification : A case study in Thai Binh Province, Vietnam - Huy, Do Quang; Keeni, Minakshi; Fuyuki, Katsuhito (Asian Journal of Agriculture and Rural Development, 2024)
The current research investigates the environmental and economic impacts of the system of rice intensification. Rice, a fundamental staple in our diets, is paradoxically a significant contributor to greenhouse gas emissions, fueling global warming and climate change. A promising solution to this is the System of Rice Intensification (SRI). Embraced in Vietnam's National Determined Contribution (NDC) under the Paris Agreement, SRI aims to boost rice yields while curbing greenhouse gas emissions compared to conventional farming practices. This study focuses on Thai Binh, a key rice-producing province in the Red River Delta. Our objective is to assess the economic, environmental, and broader societal impacts of SRI versus conventional farming. We conducted a comprehensive analysis, utilizing tools such as Cost and Benefit (CBA) evaluations, Marginal Abatement Cost (MAC) calculations, and the Linkert scale to gauge the effects. Data from 175 farmers in Phu Luong commune, Dong Hung district, Thai Binh province, formed the basis of our study. The results highlight the advantages of adopting SRI. Implementing SRI not only leads to a substantial increase of approximately 12 million Vietnamese Dong (VND) in revenue but also showcases a remarkably favorable cost of -2.7 VND for reducing 1 ton of CO2eq/ha during the transition from conventional farming. This highlights the financial and environmental benefits of SRI. Furthermore, our assessment demonstrates that SRI consistently outperforms conventional farming across economic, environmental, and societal dimensions. In essence, our findings strongly advocate for the adoption of SRI over conventional rice cultivation, as it not only mitigates environmental harm but also enhances farmers' profitability and well-being, aligning with sustainable agriculture practices and climate change mitigation efforts.